MAPPING THE POTENTIAL OF FOOD CROP BY-PRODUCTS AS FEED TO SUPPORT THE INCREASING OF BEEF CATTLE POPULATION IN MALANG DISTRICT - Aini, Fitria Nur; Likah, Sad; Nurlaili, - (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak; Vol 10 No 2 (2021): Pastura Vol. 10 No. 2 Tahun 2021DO - 10.24843/Pastura.2021.v10.i02.p08, 2021)
Malang Regency as one of regions in East Java has a large potential for the development of beef cattle population. One of the problems faced by breeders in Malang Regency was the fluctuation of forage. Using food crop by-products as feed becomes an alternative to meet the nutritional needs of livestock. This study mapped the potential of rice straw, corn straw, soybean straw, peanut straw, cassava straw and sweet potato straw as a source of feed to support the increasing of beef cattle population. The potential was determined based on the capacity of area per district due to the production of dry matter, crude protein and total digestible nutrients. The results showed that Donomulyo, Singosari and Kepanjen sub-districts had the greatest potential in increasing the population of beef cattle in average by 35.814 heads per year. Key words: beef cattle, Malang Regency, population, straw